Explaining the Uncanny in The Double Life of Véronique - Freeland, Cynthia and (Film and Philosophy, 2001)
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNTg0MC9maWxtcGhpbDIwMDE0MjY